Performance Evaluation of Concrete Pavement Slab Considering Creep Effect by Finite Element Analysis. Issue 27 (December 2018) - Liang, Siming; Wei, Ya; Wu, Zehong; Hansen, Will
Creep, as an intrinsic property of concrete material, will inevitably affect the performance of concrete pavement slabs in the field. However, the creep effect on the performances of concrete pavement slabs is far from being fully investigated. In this study, a test set-up is designed to measure the flexural creep of concrete beams exposed to both sealed and drying conditions. The measured flexural creep results are then modeled by the microprestress–solidification theory-based creep model which is incorporated into finite element analysis to evaluate numerically the creep effect on the moisture warping deformation, warping stress, and the total stress under traffic load in concrete slabs. Parameters including slab size, slab thickness, and subgrade modulus are considered. It is found that concrete creep has a significant effect on slab performance. Based on the measured creep properties in this study, the warping deformation of slabs can be reduced by 8–62%, and the warping stress and the total stress can be relaxed by at least 50%. Therefore, it is of importance to incorporate creep effect in analyzing warping deformation and stress generated in concrete pavement slabs. This study also provides a numerical methodology to the current performance evaluation of concrete slabs in the field.